Sad populism and the policies of hope - Massimo Morelli (EconPol Forum, 2024)
The erosion of trust in liberal representative democracy, institutions, and parties generated a shift to commitment politics, in which identitarian and nationalist protection commitments are perceived as feasible (right-wing populism), whereas left-wing welfare policy commitments as not credible during times of low fiscal space. People who demand commitments by the executive power may want the weakening of all other powers, which are perceived as obstacles for such desired policy commitments: a dangerous path from economic populism to illiberal populism. This populist time is characterized by two paradoxes: a political paradox (demand for fewer checks and balances at a time of growing distrust) and an economic paradox (greater demand for national sovereignty in times of global challenges, not solvable by nation-level policies). Distrust goes hand in hand with low hopes and aspirations. It is difficult to invert the trend at the national level, but carefully chosen European policies can achieve it. Corporate and capital taxation at the EU level is feasible and could give resources for greater economic security of the masses, e.g., with an EU unemployment insurance scheme, while at the same time helping to reduce national-level labor income taxes. This type of policy can generate trust and hope in supranational institutions.
Keywords: 330